Functional Analysis of Anti-cytokine Autoantibodies Using Flow Cytometry - Merkel, Patricia A.; Lebo, Terri; Knight, Vijaya (Frontiers in Immunology, 2019)
Autoantibodies to cytokines are increasingly being detected in association with immunodeficient, autoimmune and immune dysregulated states. Presence of these autoantibodies in an otherwise healthy individual may result in a unique phenotype characterized by predisposition to infection with specific organisms. The ability to detect these autoantibodies is of importance as it may direct treatment toward a combination of anti-microbial agents and immunomodulatory therapies that decrease autoantibody levels, thereby releasing the immune system from autoantibody-mediated inhibition. Ligand binding assays such as ELISA or bead multiplex assays have been used to detect these antibodies. However, not all anti-cytokine autoantibodies have demonstrable function in vitro and therefore their clinical significance is unclear. Assays that evaluate the functionality of anti-cytokine autoantibodies can supplement such ligand binding assays and add valuable functional information that, when viewed in the context of the clinical phenotype, may guide the use of adjunctive immunomodulatory therapy. This mini review provides an overview of anti-cytokine autoantibodies identified to date and their clinical associations. It also describes the use of flow cytometry for the functional analysis of anti-IFN and anti-GM-CSF autoantibodies.